Prenatal diagnosis of chromosomal mosaicism in over 1600 cases using array comparative genomic hybridization as a first line test. (17th February 2014) - Carey, Louise; Scott, Fergus; Murphy, Kristi; Mansfield, Nerida; Barahona, Paulette; Leigh, Don; Robertson, Rob; McLennan, Andrew
ABSTRACT Objective The aim of this study was to assess the detection of chromosomal mosaicism in chorionic villus (CVS) and amniotic fluid (AF) samples using array comparative genomic hybridization (aCGH) and quantitative fluorescent polymerase chain reaction. Methods All patients undergoing invasive prenatal testing by aCGH at a specialist prenatal screening service were included in the study. A total of 1609 samples (953 CVS and 656 AF) underwent quantitative fluorescent polymerase chain reaction and targeted aCGH without concurrent conventional G‐banded karyotyping. Results Chromosomal mosaicism was detected in 20 of the 1609 cases (1.24%); of which 17 were derived from 953 CVS (1.78%), and three from 656 AF (0.46%). Mosaicism was observed at a level as low as 9%. Four cases were likely confined placental mosaicism, 12 were likely true fetal mosaicism, and four cases were unable to be classified into either group. Conclusions This study demonstrates that the use of aCGH as a first line test is able to identify chromosomal mosaicism down to 9%, which is lower than the level reliably detected using standard cytogenetic analysis. aCGH avoids the disadvantages of culturing, which include culture bias, artifact, and culture failure. © 2014 John Wiley & Sons, Ltd.